Preparation for micro-lithium slag via wet grinding and its application as accelerator in Portland cement. (20th March 2020) - Tan, Hongbo; Li, Maogao; He, Xingyang; Su, Ying; Zhang, Junjie; Pan, Han; Yang, Jin; Wang, Yingbin
Abstract: Industrial wastes consumed by the preparation of building materials is a potential method to ensure the sustainable development. In this study, lithium slag (LS), as the by-product of lithium salts production, was treated by wet grinding process to prepare micro particles and used to expedite the early hydration of Portland cement (PC). The physical-chemical properties of micro-lithium slag (micro-LS) was characterized comprehensively. Binary system of PC and micro-LS was designed and its compressive strength at 16 h, 1day, and 28 days was measured. The hydration process was observed by hydration heat. Hydrates trait was investigated by XRD, TG-DTG, and NMR; pores structure was estimated by MIP and SEM. Results showed that the micro-LS with D50 = 300 nm was obtained by wet grinding, in which the crystalline was far lower than the amorphous phases. More importantly, micro-LS could significantly promote the early strength of PC. 4.0% dosage increased the strength by almost 3 times at 16 h and by more than 50% at 1 day; 28 days strength was also increased by 28%, indicating that micro-LS expected to be used as an excellent accelerator for PC. The great improvement was mainly contributed to the nucleation inducing effect on hydration, the refined pore structure, and the high pozzolanic reactivity of micro-LS. The research suggested an innovation method for the utilization of LS. Highlights: Lithium slag with D50 = 300 nm could be prepared via wet-grinding. The micro-LS could act as an excellent accelerator for PC hydration. A novel way to dispose lithium slag was suggested.